On the necessity of improving the method of clusterization of vessel routes as a procedural module of the automated data production processing system in sun (Computer systems and information technologies, 2020)
The article is devoted to the analysis of the existing method of clustering of ship routes within the exclusive sea (economic) zone from the standpoint of substantiation of its application or identification of ways to improve it for use in the surface lighting system in the interests of national security at the state border.The study found that the existing method of clustering ship routes can not be explicitly applicable for use in the surface lighting system as a procedural module of the automated data processing system, which would provide a sufficient level of reliability to detect signs of violations of border legislation within the exclusive maritime ( economic) zone. It is also established that the improvement of the method of clustering of routes of ships should address the following issues: definition of such types of approximation for the formation of continuous routes of individual ships, which would provide a sufficient level of reliability of the results on given experimental data sets. time; justification for the choice of such a number of experimental points of location of ships and directly a combination of points that would ensure a sufficient level of reliability of the conclusions formed; study of different metrics to establish the similarity of arbitrary routes of ships from the standpoint of ensuring unambiguous conclusions; adaptation of the proposed tools to the boundary initial conditions of the studied problem; adaptation of the method for the case of arbitrary complexity of the route of vessels; formation of such a method of constructing a reference route within the desired cluster, which would ensure the reproduction of the route in the form of a continuous trajectory.
Keywords: surface lighting system; procedural module; automated data processing system; method; clustering; route